2003
DOI: 10.1123/jtpe.22.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Retention in an Urban Extended Day Program: A Process-Based Assessment

Abstract: Evaluations of extended day programs in underserved communities have shown that participants usually drop out by the time they are 11–12 years old. Most of these programs, especially those that focus on physical activity, do not promote broadly developmental and empowerment-based processes and outcomes advocated by the emerging field of youth development. This article investigates both the retention issue and youth development processes and outcomes for two sequential physical activity extended day programs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
34

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 0 publications
6
35
0
34
Order By: Relevance
“…Support from a caring adult emerged as a significant predictor variable in all three regression models. This finding is consistent with previous studies on physical activity programs with urban youth Hellison and Wright 2003;Schilling 2001). Studies of programs delivered in extended day and sport camp settings have highlighted the importance of a supportive and committed program leader (Hellison and Wright 2003;Schilling 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Support from a caring adult emerged as a significant predictor variable in all three regression models. This finding is consistent with previous studies on physical activity programs with urban youth Hellison and Wright 2003;Schilling 2001). Studies of programs delivered in extended day and sport camp settings have highlighted the importance of a supportive and committed program leader (Hellison and Wright 2003;Schilling 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Una característica a destacar fue que los jóvenes de mayor edad adquirían el rol de líderes y responsables de grupos de menor edad, lo que les permitía trabajar las conductas de liderazgo. Los resultados de este estudio mostraron un aumento de las conductas de responsabilidad personal y de las habilidades sociales, así como la transferencia de estos comportamientos a otras esferas de su vida cotidiana (Hellison, y Wright, 2003).…”
Section: Investigaciones Precedentes Que Han Desarrollado Programas Dunclassified
“…One example of such an explanation was that the sports coaches continuously discussed the transference of self-direction and goal setting from the sports setting to other settings (Anderson-Butcher, Riley, Amorose, Iachini, & Wade-Mdivanian, 2014;Walsh et al, 2010). Other authors suggested that improvements in social responsibility may be explained by the involvement of caring sports coaches (Hellison & Wright, 2003), the inclusion of a life skill education part (Riley & Anderson-Butcher, 2012), and the presence of negative events, like injuries, that provide opportunities to develop empathy (Holt et al, 2012). Besides studies on sports programs based on the TPSR model, two other studies showed improvements in social responsibility skills.…”
Section: Social Life Skillsmentioning
confidence: 99%